2016
DOI: 10.1097/scs.0000000000003022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Degree of the Mastoid Pneumatization on Cartilage Type 1 Tympanoplasty Success

Abstract: The degree of mastoid pneumatization did not affect the success rate of cartilage type 1 tympanoplasty. Further studies with larger numbers of patients are needed to evaluate the relationship between the degree of the mastoid pneumatization and anatomical outcomes after placement of various graft types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Yegin et al . 2 examined the effect of mastoid pneumatisation on graft success in type 1 tympanoplasty in adult patients and concluded that the degree of mastoid pneumatisation did not affect the operation's success.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yegin et al . 2 examined the effect of mastoid pneumatisation on graft success in type 1 tympanoplasty in adult patients and concluded that the degree of mastoid pneumatisation did not affect the operation's success.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, various factors are reported to affect surgical outcomes in tympanoplasty, such as age, perforation size and location, condition of the contralateral ear, graft type, and middle-ear and mastoid bone pneumatisation. 1,2…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations